2017
DOI: 10.1038/nature21375
|View full text |Cite
|
Sign up to set email alerts
|

Newly born peroxisomes are a hybrid of mitochondrial and ER-derived pre-peroxisomes

Abstract: Peroxisomes function together with mitochondria in a number of essential biochemical pathways, from bile acid synthesis to fatty acid oxidation. Peroxisomes grow and divide from pre-existing organelles, but can also emerge de novo in the cell. The physiological regulation of de novo peroxisome biogenesis remains unclear, and it is thought that peroxisomes emerge from the endoplasmic reticulum in both mammalian and yeast cells. However, in contrast to the yeast system, a number of integral peroxisomal membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
345
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(358 citation statements)
references
References 38 publications
13
345
0
Order By: Relevance
“…It was instrumental in showing that peroxisomes can be formed de novo from ER membranes [34,35,37]. However, the indications for a mitochondrial connection recently demonstrated in human fibroblasts by the group of McBride [11] have not been observed in yeast. How can this be?…”
Section: Recent Findings: Mitochondrial Membranes Are Involved In Biomentioning
confidence: 99%
See 1 more Smart Citation
“…It was instrumental in showing that peroxisomes can be formed de novo from ER membranes [34,35,37]. However, the indications for a mitochondrial connection recently demonstrated in human fibroblasts by the group of McBride [11] have not been observed in yeast. How can this be?…”
Section: Recent Findings: Mitochondrial Membranes Are Involved In Biomentioning
confidence: 99%
“…These vesicles fuse with Pex16 containing ER-derived vesicles to give rise to de novo peroxisomes (as defined by import of peroxisomal proteins) [11]. In the "News & Views" accompanying the article, Hettema and Gould pinpoint differences between de novo peroxisome formation in mammalian cells and yeast [12].…”
Section: Recent Findings: Mitochondrial Membranes Are Involved In Biomentioning
confidence: 99%
“…The extent of interaction is so high that it was suggested that peroxisomes have a mitochondrial origin and that they emerged as functionally specialized mitochondria [100]. Indeed, new evidence now demonstrates that pre-peroxisomal vesicles bud from mitochondria [101].…”
Section: Mitochondria-peroxisomesmentioning
confidence: 97%
“…Moreover, mammalian PEX3 can be inserted into the mitochondrial outer membrane, and mitochondrion-derived preperoxisomal vesicles can fuse with PEX19-containing ERderived preperoxisomal vesicles to form import-competent peroxisomes (Sugiura et al, 2017).…”
Section: Peroxisome Genesis Membrane Protein Insertion and Budding Frmentioning
confidence: 99%